The Relationship Between Personality Traits and Person-Job Fit : A Case of University Malaya Medical Centre (UMMC) - Dahlia, Suhaimi (2012)
Personality traits are a vital element in determining compatibility between person and job in an organization. This research was designed to investigate the relationship between individual’s personality traits namely agreeableness,conscientiousness, extraversion, neuroticism and openness to experience and person-job fit. This study used quantitative research methodology in investigating the said relationship in a government healthcare service provider – University Malaya Medical Centre (UMMC). Through distribution of questionnaires, a total of 294 employees of various job positions located in different departments made up the case of the research. The findings of this research confirmed a slight significant relationship between agreeableness, conscientiousness and combination of all personality traits (agreeableness, conscientiousness, extraversion, neuroticism and openness to experience) with person-job fit.On the other hand, extraversion, neuroticism and openness to experience indicated insignificant relationship with person-job fit. This study has renewed the importance of micro level analysis of an organization i.e. individual. Besides, this study has added to the area of knowledge which is still empirically scarce.